Increasing supply chain performance in digital society - Leon, Ramona-Diana, 1986-; Rodriguez, Raul, 1976-; Alfaro-Saiz, Juan-Jose, 1968- (Advances in logistics, operations, and management science (ALOMS) book series., 2022)
"This book presents innovative approaches to measure, manage and project towards the future of the digital capabilities of supply chains and the relationship these have with performance (at the operative, tactic and strategic level), not only where they are today but also where they may be in the medium/long-term and the resources they need to get there"--